ROLE OF INDIAN GOVERNMENT POLICIES IN SUPPORTING SMES AGAINST EXCHANGE RATE RISKS - Harshita (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The economy of India is driven by Small and Medium Enterprises (SMEs), which contribute almost 45 percent of the total imports and exports of the country, and provide significant employment opportunities. This essential role notwithstanding, SMEs are still very susceptible to external shocks, especially those that concern exchange rates. The volatility of the rupee against the major currencies, particularly the US dollar, can also negatively impact their profitability by increasing the cost of inputs of firms that are import-driven and decreasing the competitiveness of exports when the rupee appreciates. In response to these challenges, the Indian government, in consultation with the Reserve Bank of India (RBI), has enacted various policies and institutional arrangements to assist SMEs in dealing with currency risk. These are ease of access to hedging instruments like forward contracts and options, the credit insurance plans offered by the Export Credit Guarantee Corporation (ECGC), interest subsidies on the Interest Equalisation Scheme (IES), and preference sector lending. Also, export promotion programs such as the Merchandise Exports from India Scheme (MEIS) and its predecessor, RoDTEP, provide relief on taxes and competitiveness. Awareness and training also enhance the capacity of SMEs to address risk. Although certain advances have been achieved, there are still gaps in awareness, adoption, and access, and further reforms are needed.